Combining free tissue transfer with pedicled flap in reconstruction of extensive oromandibular malignancy defects: a clinical study - Narayan, Naveen; Manakchand, Kamal Kumar (International Surgery Journal, 2020)
Background: Extensive composite defects of the oromandibular site involve skin, mandible, soft tissue and oral mucosa. Though many opine that with the coming on of free flap surgery, the pedicled flap is an outdated surgical option, the latter still has its uses. Free flaps are criticized as being medically risky, expensive, and time-consuming. Combining both these flaps in a single surgery would bring in the baggage of all negatives along with the benefits of these flaps. Methods: Over a period of 3 years, 13 patients with expected large composite oral defects after ablative surgery for malignancy were included in the study requiring both skin cover and mucosal lining. A one-stage reconstructive procedure employing combination of free and pedicled flaps was used. Data was abstracted pertaining to cancer demography and surgical outcome. Results: The free fibula osteocutaneous flap (FFOCF)- deltopectoral fasciocutaneous flap (DPF) combination was most commonly used (n=5), secondly by free radial forearm flap (FRAFF)-DPF combination (n=4), FRAFF- pectoralis major myocutaneous flap (PMMF) amalgamation and FFOCF-PMMF (n=2). The complete flap survival rate was 88.5 percent with 3.8% percent total (1 of 26 flaps) and 7.7% partial (2 of 26 flaps) flap failures. Minimum follow-up period was 6 months with 2 (7.7%) recurrences and 2 (7.7%) mortalities. Conclusions: We believe that in combined use of free-flap and pedicled flap procedure for one-stage reconstruction of massive mandibular defects with through-and-through cheek defects is justified because it is safe and effective and improves the quality of life for these patients albeit a bit prolonged surgery which can effectively be shortened with 2 reconstructive team approach as in our study.